Determination of SPF Value of Extract and Fraction Gel Corncob (Zea mays L.) - Indri Kusuma Dewi; Nur Atikah; Pramita Yuli Pratiwi; Oemeria Shitta Subadra; Muhammad Anugerah Alam Waris (HAKTI : Indonesian Acupuncture Therapists Association, 2025)
The climate in Indonesia, which tends to be hot due to sunburn, can cause various skin problems. Although sunlight can be beneficial in the synthesis of vitamin D for the body, its adverse effects can also cause atrophy, pigment changes, wrinkles, sunburn, and malignancy (cancer), so the use of sunscreen is essential. The development of cosmetics now leads to natural ingredients, one of which is corn cobs. Corn cobs contain phenolic compounds that have been proven to have the ability as antioxidants that play a role in preventing the adverse effects of sunlight. This study aimed to determine the extract and water fraction SPF value and corncob chloroform originating from the Klaten area. This research was conducted in-vitro using UV-Vis spectrophotometry to assess the SPF of the test material. The results showed that the average SPF of the extracted gel, chloroform fraction gel, and corncob water fraction gel were 9.92; 9.56; 9.08, which means that corn cobs have sunscreen with a maximum SPF value category (SPF between 8-15).